Feeder Pig Nursery Cost Return Projection - Dhuyvetter, Kevin C.; Tokach, Mike D.; Jones, Rodney (My University, 1996)
This publication provides estimated cost and returns for a feeder pig nursery.
MF2151_1996_10
Keywords: MF2151; Livestock; Economics; MF